S.N.U.F.F.: утопiя / В. О. Пелевин - Пелевин Виктор Олегович (Эксмо, 2012)
Фактическая дата выхода в свет: 2011 Экземпляры: аб. (2012) / Инвентарный номер: 48504 / Цена: / Сис.шифр: 84 (2Рос=Рус)6 / Авт.знак: П 24 / ГРНТИ: 17 / ББК: 84(2Рос=Рус)6